RNF213 and GUCY1A3 in Moyamoya Disease: Key Regulators of Metabolism, Inflammation, and Vascular Stability - Mineharu, Yohei; Miyamoto, Susumu (Frontiers in Neurology, 2021)
Moyamoya disease is an idiopathic chronically progressive cerebrovascular disease, which causes both ischemic and hemorrhagic stroke. Genetic studies identified RNF213/Mysterin and GUCY1A3 as disease-causing genes. They were also known to be associated with non-moyamoya intracranial large artery disease, coronary artery disease and pulmonary artery hypertension. This review focused on these two molecules and their strong linker, calcineurin/NFAT signaling and caveolin to understand the pathophysiology of moyamoya disease and related vascular diseases. They are important regulators of lipid metabolism especially lipotoxicity, NF-κB mediated inflammation, and nitric oxide-mediated vascular protection. Although intimal thickening with fibrosis and damaged vascular smooth muscle cells are the distinguishing features of moyamoya disease, origin of the fibrous tissue and the mechanism of smooth muscle cell damages remains not fully elucidated. Endothelial cells and smooth muscle cells have long been a focus of interest, but other vascular components such as immune cells and extracellular matrix also need to be investigated in future studies. Molecular research on moyamoya disease would give us a clue to understand the mechanism preserving vascular stability.